Phytochemical Screening, Antioxidant, Antidiabetic and Anticancer Activities of Elaeocarpus variabilis Fruit - Venkatachalam Balamurugan; Manikandan Sridhivya; Ramachandran Dharani; Subramaniam Selvakumar; Krishnan Vasanth (Turkish Journal of Agriculture: Food Science and Technology)
This study focused on the determination of secondary metabolites to an evaluation of the biological activity of Elaeocarpus variabilis Zmarzty fruit extract, an endemic medicinal plant. Their total Phenolic, tannin, flavonoids, alkaloids and saponins contents were quantified and their antioxidant activity, determined by DPPH, total antioxidant, ABTS, FRAP and Fe2+ chelating activity. The ethyl acetate extract exhibited the highest radical scavenging activity. The most relevant contents in total phenolics (Gallic Acid Equivalent mg/g), tannin (Gallic Acid Equivalent mg/g), total flavonoids (Rutin equivalent mg/g), total alkaloids (Quinine equivalent mg/g), and total saponin (Diosgenin equivalent mg/g) were observed. Significant correlations were established between antioxidant activity and secondary metabolites. Though the in vitro anti-diabetic activity was carried out using -amylase and -glucosidase inhibition, this indicates that the absorption and digestion of carbohydrates would probably reduce the blood glucose levels and hence help the management of type-2 diabetes. The ethyl acetate extract exhibited the potential of anticancer activity on human HT-29 colon cancer cell line IC50 values (30.0 ± 1.0) the valuable activity that compared to doxorubicin (17.0 ± 0.5). While this is the first study concerning extract from E. variabilis, our findings highlighted the richness’ in flavonoids of those extracts and their amazing potential as a source of antioxidant, anti-inflammatory, anti-diabetic, and anticancer agents.